2013
DOI: 10.1371/journal.pone.0056608
|View full text |Cite
|
Sign up to set email alerts
|

Norovirus Diversity in Diarrheic Children from an African-Descendant Settlement in Belém, Northern Brazil

Abstract: Norovirus (NoV), sapovirus (SaV) and human astrovirus (HAstV) are viral pathogens that are associated with outbreaks and sporadic cases of gastroenteritis. However, little is known about the occurrence of these pathogens in relatively isolated communities, such as the remnants of African-descendant villages (“Quilombola”). The objective of this study was the frequency determination of these viruses in children under 10 years, with and without gastroenteritis, from a “Quilombola” Community, Northern Brazil. A t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
23
3
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 47 publications
5
23
3
1
Order By: Relevance
“…These regions are approximately 2,300 km apart from each other. In contrast to our results, the study in the North showed twice the number of NoV cases in children with diarrhea but did not find the virus in any of the asymptomatic children [25]. This study complements earlier studies with hospitalized patients or outpatients at emergency rooms that involved patients with a more severe clinical profile [3].…”
Section: Discussioncontrasting
confidence: 51%
See 4 more Smart Citations
“…These regions are approximately 2,300 km apart from each other. In contrast to our results, the study in the North showed twice the number of NoV cases in children with diarrhea but did not find the virus in any of the asymptomatic children [25]. This study complements earlier studies with hospitalized patients or outpatients at emergency rooms that involved patients with a more severe clinical profile [3].…”
Section: Discussioncontrasting
confidence: 51%
“…However, a third the cases here consisted of GI, a rate that can be considered relatively high for Brazil since previous studies have described lower frequencies [3], [42], [43] as well as the Quilombola study in the North [25], although Soares et al (2007) [44] described a GI prevalence of 47.6% in Brazil.…”
Section: Discussionmentioning
confidence: 55%
See 3 more Smart Citations